Social Media Usage and Undergraduate Students’ Research Skills Development in Tai Solarin University of Education, Nigeria - Adenaike, Fausat A.; Peleyeju, Joshua O. (NIU Journal of Social Sciences, 2018)
This study examined the influence of social media usage on undergraduate students’ research skills development in Tai Solarin University of Education, Ijagun, Ogun State, Nigeria. A descriptive correlation design of the ex post facto type was adopted. 1000 undergraduate students participated in the study. Four hypotheses were formulated while a researcher’s developed questionnaire tagged ‘Social Media and Undergraduate Students’ Research Skills Questionnaire (SMUSRSQ)’ was used to gather relevant data. Analysis of Variance (ANOVA) was used as a test for all the hypotheses at .05 level of significance. The study revealed that there is significant influence of social media usage on undergraduate students’ ability to generate ideas about areas of research interest, source for quality research materials, source appropriate research analytical tools for their result presentation and develop creative writing research skills. It was recommended that universities should build and integrate interactive learning tools as well as links to research data bases to make the use of social media relevant to students’ research needs. There is also the need to sensitize students with effective utilization of social networks for more academic oriented activities. Keywords: Social Media, Usage, Undergraduate Students, Research Skills, University, Education